Sistem Kontrol Dan Monitoring Hidrogen - Oksigen (HHO) Generator Berbasis Internet Of Things (IoT) - Putra, Chandra Syah (Politeknik Negeri Lhokseumawe, 2024)
Electrolysis is a way to separate water (H2O) into hydrogen (H2) and oxygen (O2) gas by using an electric current through the water. The aim of this research is to create an Internet of Things (IoT) based prototype system that can monitor and control the hydrogen gas (H2) production process using the water electrolysis method. This research was carried out in several stages starting with a technology survey, then continuing with prototype design (including hardware design, software design, and circuit schematic design). This monitoring system device is designed with 3 sensors, namely: MQ-8 gas sensor, ACS712 current sensor, and BME280 pressure-temperature sensor. The MQ-8 sensor is set with a reading scale of 200-1000 ppm (parts per million) with an RMSE value obtained of 0.0288%. The ACS712 current sensor has an accuracy of 88.35% with a reading scale of 0-3.3 amperes, and the BME280 sensor has an accuracy of 94.47% for temperature and 99.37% for pressure with an ambient air reading scale. The results of water electrolysis testing of the entire system show that the system can work well in measuring parameters in accordance with the data sheet provisions, as well as providing flexibility in monitoring for users via smartphone.